PATTERN MAINTENANCE GROUP OF MUSLIM IDENTITY IN THE VILLAGE OF RIVER DISTRICT JALAU KAMPAR NORTH DISTRICT KAMPAR - ", Risnidawati; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted in the village of River North Jalau Kampar Kampar district. The purpose of this study was to determine the identification of members of Muslim groups and behavior patterns executed in maintaining group identity by Muslim groups. The approach used in this research is descriptive qualitative research. This makes the entire study population as research subjects. The subjects of this study amounted to 10 heads of household. Instrument Data is interview, observation and documentation. These results indicate that the Muslim group identification can be seen from the style of dress, activity in daily life and life in society. The members of the Muslim group has its own style of dress or appearance, in contrast to other Muslim communities in the village of Jalau River. Apart from that there are actions or behaviors perpetrated by Muslim groups that aims to maintain its identity. And the actions carried out by Muslim groups have reasons or specific values why it was committed.Keywords: maintenance of identity, social groups